Controlled Tensile Strain of Ge Films Hetero-Epitaxially Grown on Si Substrates Using E-Beam Evaporator. (19th November 2014) - Ki, Bugeun; Kim, Kyung Ho; Oh, Jungwoo
Abstract : Optical interconnection is projected to replace Cu wires as the data bandwidth exceeds the capacity of application processors. For compatibility with Si technologies, hetero-epitaxially grown Ge-on-Si is appropriate platform for fabricating optical sources. We investigated the effect of two-step growth on the strain in the epitaxial Ge-on-Si using an ultra-high vacuum E-beam evaporator. A low temperature regime produced a smooth Ge buffer layer without three-dimensional and a high growth temperature regime induced tensile strain in the epitaxial Ge films. The initial 0.10% of tensile stain on the as-grown Ge films was further increased to 0.23% after subsequent post-annealing.